2020
DOI: 10.1063/5.0021081
|View full text |Cite
|
Sign up to set email alerts
|

A memory window expression to evaluate the endurance of ferroelectric FETs

Abstract: The recent discovery of ferroelectricity in HfO2 has revived the interest into non-volatile memories based on ferroelectric transistors (FeFETs). The key advantages of these FeFETs include the low power consumption and the compatibility with the existing CMOS process. On the other hand, issues related mainly to endurance still represent a challenge to the development of the technology. In this Letter, we propose to exploit an analytical expression for the Memory Window (MW) as a simple yet effective characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…The proposed MFMIS FeFET with the spherical recess channel transistor (hereinafter referred to as MFMIS SR‐FeFET) is applied, as shown in Figure a. The IDSVGS characteristics and quantified parameters of the proposed SR‐FeFET can be obtained by numerical iteration, which is proposed by Miller and McWhorter, [ 1,36,37 ] and the results and details of this process will be discussed later in the main text. By introducing an additional metal layer between the ferroelectric layer and the insulator, it is possible to realize an MFMIS gate stack whose equivalent circuit is the same as that of the MFIS gate stack.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed MFMIS FeFET with the spherical recess channel transistor (hereinafter referred to as MFMIS SR‐FeFET) is applied, as shown in Figure a. The IDSVGS characteristics and quantified parameters of the proposed SR‐FeFET can be obtained by numerical iteration, which is proposed by Miller and McWhorter, [ 1,36,37 ] and the results and details of this process will be discussed later in the main text. By introducing an additional metal layer between the ferroelectric layer and the insulator, it is possible to realize an MFMIS gate stack whose equivalent circuit is the same as that of the MFIS gate stack.…”
Section: Resultsmentioning
confidence: 99%
“…The IDSVGS characteristics of the proposed device were obtained by numerical simulation based on the physics of ferroelectric nonvolatile memory transistor. [ 1,36,37 ] Then, various parameters, such as memory window (MW), electric field in the HfO 2 ferroelectric, and EDE, are extracted as a function of the CDE/CFE and Pnormals value. This work presents the guideline of gate stack for large MW and high reliability FeFETs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the maximum read memory window is limited to ∼2 V c . [ 44,78 ] As 2 V c of a typical HfO 2 ‐based FE film has a limited range of 2‐4 V, this is far lower than the target value for an FE‐NAND flash device (∼6 V). In particular, a maximum Δ V th of ∼4 V should be achieved for a TLC or QLC drive.…”
Section: Fundamentals Of Fe Film and Fefet Operationmentioning
confidence: 97%
“…Such traps and other types of generated defects are critical and can degrade the memory window during the projected lifetime. Recent studies such as [26], [27] aimed at investigating and modeling the impact of interface and oxide traps on the memory window at both device and system levels, respectively. In addition, charge trapping and detrapping at Si-SiO 2 interface plays an important role in degrading the memory window and it has shown that controlling the charge trapping and the resulting imprinting is necessary in order to ensure the reliability of the FeFET [28].…”
Section: Low-vth Curvementioning
confidence: 99%